The partisan costs of automatic voter registration. (April 2023) - Seljan, Ellen; Lochner, Todd; Webb, Alex
Abstract : Automatic Voter Registration (AVR) has been widely adopted in the US States in the last decade. Early research on this innovation suggests positive consequences for diversifying and increasing voter rolls and voter turnout (McGhee and Romero 2019; Gronke and Seljan 2020). This paper examines an additional, unintended consequence: effects on party registration. Examining the state of Oregon, a state with back-end AVR, we document a significant decreases in partisan voter registration rates. We achieve a causal estimate of this decline by making use of a natural experiment: due to historical statute, individuals with even birth years are more likely to be registered via AVR in even-numbered years compared to individuals with odd birth years. In addition to calculating a negative effect on partisan registration, we track voters registered by AVR over time to gauge the extent to which the absence of party registration is corrected over subsequent years. The conclusions of our paper have significant implications for participation in closed political primaries as well as wider partisan mobilization efforts.